Insidious [videorecording (Blu-Ray)] - Wan, James, 1977-; Wilson, Patrick, 1973-; Byrne, Rose; Shaye, Lin, 1944-; Whannell, Leigh, 1977-; Hershey, Barbara, 1948- (Columbia TriStar Home Entertainment, 2011)
Josh and Renai have a happy family, until tragedy strikes their young son, and he begins to experience things that science cannot explain. Now they must try to prevent evil spirits from trapping their comatose child in a realm called The Further.